Minority Shareholder Protection: Comparative Analysis of Restructuring Laws in Indonesia and Thailand - Yauwnes Angel Wibowo (Legtimacy: Journal of Law and Islamic Law, 2026)
Corporate restructuring, including mergers and spin-offs, inherently risks minority shareholder expropriation, particularly within Indonesia's highly concentrated ownership structures. The Indonesian Company Law exhibits a critical regulatory lacuna regarding objective valuation dispute mechanisms and equitable spin-off compensation frameworks. Employing a doctrinal legal research design with a functional comparative approach, this study evaluates the institutional efficacy of Indonesia's framework against Thailand’s progressive 2023 Civil and Commercial Code amendments. The analysis systematically reveals that Thailand’s automatic deadlock resolution mechanism successfully mitigates valuation disputes by mandating independent appraiser intervention within a strict fourteen-day statutory timeframe, thereby eliminating minority hold-out problems and managerial tunneling. Conversely, Indonesia currently relies heavily upon costly, protracted, and highly asymmetric judicial litigation processes. To ensure substantive justice and align with ASEAN Corporate Governance Scorecard standards, the Indonesian regulatory regime urgently requires legislative amendments incorporating an automated independent valuation mechanism with a binding thirty-day resolution deadline for all corporate restructuring actions.